Aircraft‐based observations of atmospheric boundary‐layer modification over Arctic leads. (3rd June 2015) - Tetzlaff, A.; Lüpkes, C.; Hartmann, J.
Abstract : Leads are elongated channels in sea ice which play an important role for the heat and moisture exchange between the polar ocean and atmosphere. The aircraft campaign STABLE aimed to improve our current understanding of the formation of convective plumes over leads and their impact on the polar atmospheric boundary layer. It was carried out over the pack ice in the northern Fram Strait in March 2013. We present case studies of the boundary layer modification and turbulent fluxes over four wide leads, which differed strongly with respect to lead characteristics and environmental conditions. The observed near‐surface sensible heat fluxes ranged from 15 to 180 W m −2 . The leads also induced an increase of the near‐surface temperature of up to 3.2 °C and a humidity increase of up to 0.2 g kg −1 . In one of the cases, large entrainment fluxes exceeding 30% of the surface fluxes were observed. Vertical profiles of turbulent sensible heat and momentum fluxes were nonlinear downstream of the leads with a distinct flux maximum in the core of the convective plumes. In two cases, the plumes also strongly affected the wind field within the atmospheric boundary layer. Low‐level jets that existed in those cases in the region upstream of the leads disappeared in the plume region. Finally, it is shown that large errors can occur when flux measurements are derived from lead orthogonal flight legs only. Therefore, complex flight patterns, as presented in this study, are necessary to accurately determine the energy fluxes in the environment of leads.